Textiles and the Creative Possibilities of Assemblage Thinking in Early Childhood: A Narrative Look - Dunnington, Catherine-Laura (International Journal for Talent Development and Creativity, 2023)
As textiles continue to feature heavily in discussions of sustainability, and young students continue to be positioned as saviors of the planet, this paper joins the call for assemblage thinking in early years research that decenters humans and foregrounds relationships. What follows is a subset of a larger study, where one preschool classroom engaged with textile themed provocations, and I had the honor of listening deeply to the children. This work borrows from sociomaterialism and artistic listening to consider what themes emerged when I considered child/textile as entangled in meaning making in one senior preschool classroom. I highlight ways in which the themes of connect, know, and perceive all surface in one richly detailed narrative of children making meaning with textiles. Finally, I offer a way in which research can support this kind of assemblage thinking in the classroom, by looking to relationships between themes and how we might represent those relationships in more nuanced, illustrative ways.